A New Approach to Determine the Total Airborne N Input into the Soil/Plant System Using 15N Isotope Dilution (ITNI): Results for Agricultural Areas in Central Germany - Rolf W.B. Russow; Frank Bahme; Heinz-Ulrich Neue (The Scientific World Journal)
The atmospheric deposition of nitrogen (N) in the environment is of great concern due to its impact on natural ecosystems including affecting vegetation, reducing biodiversity, increasing tree growth in forests, and the eutrophication of aquatic systems. Taking into account the average annual N emission into the atmosphere in Germany of about 2 million t N (ammonia/ammonium, NOx), and assuming homogeneous distribution throughout Germany, an average N deposition of 45 kg/ha x year can be calculated. Such high atmospheric N deposition could be confirmed by N balances from long-term field experiments in Central Germany (e.g., the Static Fertilization Experiment in Bad Lauchstädt). By contrast, estimates by standard methods indicate a deposition of only about 30 kg N/ha x year. This is because the standard methods are using wet-only or bulk collectors, which fail to take into account gaseous deposition and the direct uptake of atmospheric N by aerial plant parts. Therefore, a new system was developed using 15N isotope dilution methodology to measure the actual total atmospheric N input into a soil/plant system (Integrated Total Nitrogen Input, ITNI). A soil/plant system is labeled with [15N]ammonium-[15N]nitrate and the total input of airborne N is calculated from the dilution of this tracer by N from the atmosphere. An average annual deposition of 64 ± 11 kg/ha x year from 1994–2000 was measured with the ITNI system at the Bad Lauchst?dt research farm in the dry belt of Central Germany. Measurements in 1999/2000 at three other sites in Central Germany produced deposition rates of about 60 kg/ha x year. These data clearly show that the total atmospheric N deposition into the soil/plant system determined by the newly developed ITNI system significantly exceeds that obtained from standard wet-only and bulk collectors. The higher atmospheric N depositions found closely match those postulated from the N balances of long-term agricultural field experiments.